Combination intravenous immunoglobulin, oral prednisone, and methotrexate for managing scleromyxedema: case report and literature discussion - Gaia Fasano; Giancarlo Valenti; Domenico D'Amico; Mario Valenti (Dermatology Reports, 2023)
Scleromyxedema (SMX), the generalized and sclerodermic form of lichen myxedematous (LM), is a chronic mucinosis characterized by cutaneous manifestation and several systemic comorbidities. Treatment options are limited and there are no definitive therapeutic guidelines. We report a case of a 48-year-old man with scleromyxedema, associated with monoclonal gammopathy and arthritis, who has been successfully treated with intravenous immunoglobulins (IVIg), oral corticosteroids, and methotrexate (MTX). IVIg is the most used first-line therapy for SMX based on its efficacy and well-tolerated nature and has been used for a growing number of skin disorders. In our case, combining IVIg with oral prednisone and MTX allowed better control of skin disease and extra-cutaneous manifestations. To the best of our knowledge, this is the first case of a successful treatment for SMX with a combination of therapeutic strategies and a good safety profile.